2017
DOI: 10.1016/s1474-4422(16)30339-8
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic genetic effects influencing sleep and neurological disorders

Abstract: Research evidence increasingly points to the large impact of sleep disturbances on public health. Many aspects of sleep are heritable and genes influencing traits such as timing, EEG characteristics, sleep duration, and response to sleep loss have been identified. Notably, large-scale genome-wide analyses have implicated numerous genes with small effects on sleep timing. Additionally, there has been considerable progress in the identification of genes influencing risk for some neurological sleep disorders. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 112 publications
(199 reference statements)
1
48
0
Order By: Relevance
“…There is a strong body of evidence indicating that SHANK3 , which encodes a post-synaptic scaffolding protein, influences the combined phenotype of autism spectrum disorder symptoms with sleep disturbances and intellectual disability. Recently Veatch and colleagues have hypothesized that genes involved in synaptic homeostasis, including the processes of synaptic development and pruning, may be involved in both ASD and sleep-wake control, offering a promising shared mechanism [55•]. Investigators suggest that a greater understanding of the pleiotropic roles of genes influencing both sleep and neurological disorders could lead to new treatment strategies for children with ASD [55•].…”
Section: What Are the Hypotheses For The High Prevalence Of Insomnia mentioning
confidence: 99%
“…There is a strong body of evidence indicating that SHANK3 , which encodes a post-synaptic scaffolding protein, influences the combined phenotype of autism spectrum disorder symptoms with sleep disturbances and intellectual disability. Recently Veatch and colleagues have hypothesized that genes involved in synaptic homeostasis, including the processes of synaptic development and pruning, may be involved in both ASD and sleep-wake control, offering a promising shared mechanism [55•]. Investigators suggest that a greater understanding of the pleiotropic roles of genes influencing both sleep and neurological disorders could lead to new treatment strategies for children with ASD [55•].…”
Section: What Are the Hypotheses For The High Prevalence Of Insomnia mentioning
confidence: 99%
“…[Insert Table 1 about here] MRI acquisition. Diffusion tensor imaging scans were acquired at two Siemens scanners (Siemens Medical Solutions, Erlangen, Germany), a 1.5 T Avanto (n=64, 70% female, mean age (SD, min-max) = 51 (13, years), TR/TE=8200/81 ms, FOV=128, 60 diffusion-sensitizing gradients at a b-value of 700 s mm −2 and 2 volumes without diffusion weighting (b-value = 0)), and 3T Skyra scanner (n=187, 58% female, mean age (SD, min-max) = 55 (22, years), TR/TE=9200/87 ms, FOV=130, 64 diffusion-sensitizing gradients at a b-value of 1000 s mm −2 and 1 volume without diffusion weighting. The sequences and scanner were the same across the two time points for each participant.…”
Section: Figurementioning
confidence: 99%
“…While a consortium study showed that worse self-reported sleep related to hippocampal atrophy 8 , integrity measured by diffusion tensor imaging (DTI) may detect more subtle microstructural decline 9 , and hippocampal mean diffusivity (MD) has demonstrated particularly sensitive to memory 10,11 . Sleep-hippocampal integrity relationships could also reflect effects of the APOE ε4 genotype 12 , or of common genetic variation affecting sleep and hippocampus 13 . Testing whether worse self-reported sleep relates to memory decline and more rapid reduction of hippocampal integrity while controlling for genetic variation, and whether such relationships are stronger in older adults with pathological levels of Aβ, will help us understand the role of sleep problems in early AD-related pathology.…”
mentioning
confidence: 99%
“…Narcolepsy is a neurologic disease characterized by involuntary and irresistible “sleep attacks” that can occur while talking, standing, walking, eating and driving (Veatch, Keenan, Gehrman, Malow, & Pack, ). This excessive sleepiness is typically associated with cataplexy (sudden bilateral skeletal muscle weakness), which is often provoked by strong emotion and lasts no longer than a few minutes.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Moreover, the anti‐narcoleptic drug Modafinil activates orexin neurons. In human patients, however, there is little evidence that variants in HCRT or related genes contribute to narcolepsy (Veatch et al., ). Instead, narcolepsy with cataplexy is tightly associated with HLA class II allele DQB1*0602 (Tafti et al., ) .…”
Section: Sleep Disordersmentioning
confidence: 99%